2014
DOI: 10.1007/s12013-014-0339-0
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-449a Suppresses Non-small Cell Lung Cancer

Abstract: This study was set to determine the expression of microRNA-449a in cancer tissue and serum of non-small cell lung cancer (NSCLC) patients and explore the underlying mechanisms of its tumor suppressor functions. We selected 50 NSCLC patients in our hospital as the lung cancer group and 50 healthy volunteers as the control group. RT-PCR was performed to detect the expression levels of microRNA-449a in NSCLC tissue and the plasma of NSCLC patients. Further, we transfected microRNA-449a mimic and inhibitor in lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…There are relevant studies concerning both miRNAs and NSCLC. For example, it has been reported that miR-449a expression is decreased in NSCLC, which could promote cell proliferation and inhibit apoptosis (16). Similarly, clinical data analysis has shown that decreased miR-224 and increased miRNA-96 expression in NSCLC tissues are closely related to clinicopathologic stage and a poor prognosis (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…There are relevant studies concerning both miRNAs and NSCLC. For example, it has been reported that miR-449a expression is decreased in NSCLC, which could promote cell proliferation and inhibit apoptosis (16). Similarly, clinical data analysis has shown that decreased miR-224 and increased miRNA-96 expression in NSCLC tissues are closely related to clinicopathologic stage and a poor prognosis (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Recently years, more and more miRNAs have been recognized involved in the diagnosis, prognosis and progression of different kinds of human cancers, including lung cancers [33][34][35]. MiR-449a, as an example, has been described as the suppressor of NSCLC by Ding and his colleagues in 2014 [36]. MiR-302b is one important member of these miRNAs, which belongs to the miR-302 family [37].…”
Section: Discussionmentioning
confidence: 99%
“…This nding is consistent with previous reports. For example, Ding et al demonstrated that the miR-449a expression levels in non-small cell lung cancer are signi cantly lower than those in the surrounding tissue [21]. Ren et al con rmed that miR-449a acts as a tumor suppressor and is mostly down-regulated in lung cancer patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-449a (miR-449a) is one of these miRNAs, which expressed in wide types of cancers, such as ovarian cancer, gastric carcinoma, bladder cancer and lung cancer [16][17][18][19][20]. Recent evidences suggest that miR-449a performs suppression role in non-small cell lung cancer (NSCLC), which could inhibit tumor cell proliferation and promote tumor cell apoptosis [21]. However, no related studies have reported the diagnostic value of miR-449a in lung cancer.…”
Section: Introductionmentioning
confidence: 99%